CAN ALTERNATIVE DISPUTE RESOLUTION MECHANISMS REVOLUTIONIZE CONFLICT AND DISPUTE RESOLUTION IN INDONESIA? - Subrata, Rusli (LITIGASI, 2023)
Humans, as Aristotle suggests, are inherently social beings ("zoon politicon"), driven to interact within society. However, Thomas Hobbes presents a contrasting view, describing humans as "homo homini lupus," indicating that human nature is inherently conflict-prone. The pursuit of individual interests often leads to legal conflicts, especially in Indonesia, where dispute resolution can be categorized into litigation and non-litigation methods. The 1999 Arbitration and Alternative Dispute Resolution Law (Undang-Undang No. 30 Tahun 1999) introduced a fresh perspective on conflict resolution. Yet, this law addresses only disputes, overlooking the broader concept of conflict, which often entails more complex societal issues. Additionally, many view alternative dispute resolution (ADR) as limited to civil cases, ignoring its potential application in broader contexts. This research, employing a doctrinal legal research methodology, examines the distinction between dispute and conflict and explores the role of ADR in resolving both. The findings reveal that while ADR is primarily recognized for resolving disputes, its principles can also be applied to broader conflicts that extend beyond civil matters. The novelty of this study lies in its exploration of ADR’s potential to address not only legal disputes but also more profound societal conflicts in Indonesia. The urgency of this research is underscored by the need for an inclusive, effective approach to resolving various legal and societal challenges. The study contributes to the broader understanding of ADR's potential in reshaping Indonesia’s conflict resolution landscape.